Dinâmica do nitrogênio e potássio nos resíduos culturais do milho submetido à adubação mineral - Medeiros, Léa Cristina de (2016)
At the end of cultivation, the farmer has an expressive provision in the amount of crop residues, not rare, reaching a volume two to three times greater than the product of economic interest (grain, fruit, fiber, etc). The objective was to evaluate the rate of decomposition and release of N and K residues of maize (Zea mays) submitted to nitrogen and potassium fertilization on a Red Yellow Latossolo. The experiments of fertilization and decomposition kinetics were conducted in the years 2014 and 2015, respectively, in Chã-de-Jardim experimental area belonging to the CCA / UFPB in Areia-PB. The fertilization experiment was conducted following a randomized complete block design with 11 treatments and 5 repetitions, which were prepared using the exponential matrix Plan Puebla III, where he defined N doses (5; 30; 50; 70 and 95 kg ha-1) in the form of urea, and K (4, 24, 40, 56 and 76 kg ha-1) as KCl, plus an absolute control (without fertilizer) summing eleven treatments. Decomposition bags were used (litter bags), were installed containing agricultural waste corn (stem, leaf, and straw). Each interval of 30 days after installation, was carried out sampling a bag per plot, totaling 5 samples (30, 60, 90, 120, 150 days). Both the analysis of variance as to estimate the parameters of the exponential equation, we used the statistical package SAEG version 9.1. The productivity of the biomass of the corn response to nitrogen fertilizer (N) and potassium (K) in 2014 had a significant effect on different compartments of the plant. A reduction of 30.5% corn biomass residue, after 30 days of the soil incorporated. The nutritional status of the plant reflected in the rate of decomposition of waste materials in the soil.